HIV viral load monitoring in HIV-infected pregnant women established on antiretroviral therapy in Cape Town, South Africa - Tsondai, Priscilla Ruvimbo (Centre for Infectious Disease Epidemiology and Research (CIDER), 2017)
Background: Antiretroviral therapy (ART) services have expanded over the past decade, providing treatment to over 15 million people globally. It is imperative that this scale-up of ART provision be accompanied by optimal treatment response monitoring strategies to timely and accurately detect treatment failure. Routine viral load (VL) monitoring is the preferred ART response monitoring tool and its use has been increasing across Africa; however, there are few insights into VL monitoring practices during pregnancy. This thesis describes public sector VL testing practices in a cohort of HIV-infected pregnant women who initiated ART before pregnancy in Cape Town, South Africa. Methods: This study was conceived in 2015 as a sub-analysis of the first phase of an on-going prospective trial: the Strategies to optimize antiretroviral therapy services for maternal and child health (MCH-ART) Study, being conducted in Gugulethu, Cape Town, South Africa. Consecutive HIV-infected pregnant women on ART before pregnancy and making their first visit to a primary care antenatal clinic between March 2013 and June 2014 were enrolled into the study. Pre-existing demographic, obstetric and ART history data collected during enrolment into the MCH-ART study were used. In addition, HIV VL results were obtained from the National Health Laboratory Service (NHLS) system from 15 months prior to the estimated date of conception to delivery. VL testing and VL results were described for the two periods: (i) before conception (from estimated date of conception to 15 months prior) and (ii) during pregnancy (from estimated date of conception to delivery). Results: Among 520 women the median age was 31 years [Interquartile range (IQR), 28-35 years] and the median duration of ART use was 2.7 years [IQR, 1.5-5.1 years]. Before conception, 66% (n=311) of women had at least one VL test done in routine adult ART services, and 9% of these results (n=29) were >1000 copies/mL. During the pregnancy, 80% (n=415) of women had at least one VL test done and 12% (n=49) of these results were >1000 copies/mL. Pregnant women with elevated VL >1000 copies/mL were more likely to have been on ART for longer (p=0.049), report at least 2 missed ART doses in the preceding 30 days (p=0.043) and be on a protease inhibitorbased regimen (p=0.016). Among women with VL >1000 copies/mL during pregnancy, 59% (n=29) had a repeat VL done at a median of 3.5 months after the initial test (IQR, 2.1-4.4 months) with 52% (n=15) of these women having a VL >1000 copies/mL on this second test. Conclusion: While coverage of VL monitoring appears high in this setting, a substantial fraction of women with elevated VL in pregnancy were never retested. With increasing numbers of HIV positive women using ART, greater attention is needed to design and implement effective strategies for VL monitoring in pregnancy.